Light Scattering of Short Helix Pitch Ferroelectric Liquid Crystal - Hegde, Gurumurthy; E. P., Pozhidaev; V. G., Chigrinov; A. A., Murauski; H. S., Kwok; V. V., Vashchenko; A. I., Krivoshey (Taylor & Francis, 2009)
Two new light scattering modes have been discovered in short helix pitch (p0ﬃ350 nm) ferroelectric liquid crystal (FLC). One of the modes arises because of a special kind of the FLC structure non-uniformity that originates inherently as a new phenomenon if the helix pitch is very small. Another mode relates to the helix twisting after the driving voltage switching off